The effect of putrescine on pollen performance in hazelnut (Corylus avellana L.) - ÇETİNBAŞ GENÇ, ASLIHAN; VARDAR, FİLİZ (ELSEVIER, 2020)
One of the most substantial molecules for pollen germination and tube growth are polyamines. Putrescine is the most abundant polyamine and the molecule from which spermine and spermidine originate. In this study, the effects of different exogenous putrescine concentrations (0.05, 0.25, 0.5 and 2.5 mM) on pollen performance of hazelnut (Corylus avellana) were investigated. Germination ratio and tube length were induced by 0.05 and 0.25 mM putrescine treatment. Putrescine concentration above 0.25 mM inhibited the pollen germination, tube elongation and, caused morphological alterations such as apex swelling. While the 0.05 and 0.25 mM putrescine treatment did not cause significant change in callose accumulation and actin filament distribution at tube apex, concentrations above 0.25 mM caused dense callose accumulation and increased the actin filament anisotropy at tube apex. Moreover, putrescine treatment caused an increase of reactive oxygen species level at the apex, especially in swollen tube apex, at the concentration of 2.5 mM. Reactive oxygen species detoxification mechanisms, which can be examined by changes in the amount of hydrogen peroxide and enzyme activities, were not disrupted by 0.05 and 0.25 mM putrescine treatment, while they are affected by 0.5 and 2.5 mM putrescine treatment. Eventually, low doses (0.05 and 0.25 mM) of putrescine can be used as a performance enhancing agent for hazelnut pollen tube growth, while the higher concentrations (0.5 and 2.5 mM) cause adverse effects reducing fertilization success.
Keywords: Hazelnut; Pollen germination; Pollen elongation; Polyamine; Putrescine; TUBE GROWTH; ACTIN-FILAMENTS; SUCROSE SYNTHASE; LATRUNCULIN-B; GERMINATION; POLYAMINES; CYTOSKELETON; TEMPERATURE; STRESS; CONSTRUCTION